INNOVATION VILLAGE FOR LIVESTOCK DEVELOPMENT THROUGH FEED FERMENTATION TECHNOLOGY IN THE CITY OF TIDORE ISLANDS - Emy Saelan; Sri Lestari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Fermentation is a process of preserving feed ingredients, causing chemical changes in feed ingredients as a result of enzyme activity that produces CO2 and alcohol from for Livestock Development Through Feed Fermentation Technology in the City of Tidore Islands carried out on the development of poultry, especially the Kampong chicken. The Innovation Village activity program is carried out through training in processing bran which is waste from rice milling and is a source of crude protein for livestock. Through the Kubermas Program Kemitraan Masyarakat (PKM) activities, training on rice bran processing was carried out through fermentation techniques. The output target of PKM activities is that partner livestock groups can formulation poultry feed using fermentation techniques. The Kubermas Program Kemitraan Masyarakat (PKM) results in partner livestock groups being able to be independent in providing feed for their livestock, not depending on the manufacturer's feed